Infection Prevention Behavior Level of Dental Technicians in Dental Laboratories Yogyakarta - Putriani; Kusumastiwi, Pipiet Okti (International Journal of Health Literacy and Science, 2023)
Working in a dental laboratory risks exposure to chemicals or infectious materials. One of the activities in the dental laboratory is denture manufacturing. Dental impressions, prostheses, or improper handling of clinical materials in the dental laboratory might contaminate dental technicians with pathogenic microorganisms. Dental technicians should have basic knowledge of the transmission of infection through the dental laboratory to prevent the transmission of infectious agents from dental impressions. This research aimed to discover the level of infection prevention behavior of dental technicians in dental laboratories in Yogyakarta. This research is observational descriptive research that employs a cross-sectional design. The samples were 55 dentaltechnicians working in the three Dental laboratories in Yogyakarta. The instrument was a questionnaire used to measure the level of knowledge. The data were analyzed using univariate (descriptive). According to the findings, almost half of the respondents (42%) had a low infection-prevention behavior level. The conclusion of level infection prevention behavior among dental technicians in Yogyakarta's dental laboratories was common.